A European Cenozoic 'Macrobaenid:' New Data about the Paleocene Arrival of Several Turtle Lineages to Europe. Issue 4 (3rd July 2020) - Pérez-GarcÍa, Adán
ABSTRACT: The European Paleocene terrestrial and freshwater turtle fauna is radically different from that in the Upper Cretaceous. This Paleocene fauna is largely formed by groups of turtles not found in the Mesozoic record of the continent. However, European Paleocene sites have produced several lineages that dispersed from other continents, including basal turtles (i.e., stem Testudines) and compsemydids (i.e., Paracryptodira). Both groups are well represented at the French upper Paleocene site of Mont de Berru, Marne Department. A new taxon from this locality, Gallica lapparentiana, gen. et sp. nov., is described here and attributed to the eucryptodiran lineage 'Macrobaenidae.' Heretofore, no 'macrobaenid' has yet been identified in the Cenozoic record of Europe. 'Macrobaenids' have their origin in the Upper Jurassic of Asia. In fact, they represent the most diverse group of turtles currently known for the Lower Cretaceous record in that continent. They reach North America in the Upper Cretaceous, where they continue to diversify during the Upper Cretaceous and lower Paleocene. The first justified identification of 'Macrobaenidae' from the upper Paleocene of Europe, both in France and in Belgium, provides new data on the replacement process of European Late Cretaceous turtle fauna by new groups from other continents. http://zoobank.org/urn:lsid:zoobank.org:pub:B417CC80-F47C-4AE5-B8B2-0BAA249A177F